Epidemiology and pathogenicity of Haemophilus parasuis in eastern China - Xu, Jingyu; Jin, Xin; Li, Xuesong; Yang, Dehong (Frontiers in Microbiology, 2025)
Haemophilus parasuis (H. parasuis), the causative agent of Glässer’s disease (polyserositis), exhibits considerable serotype diversity and is globally distributed. To investigate the epidemiological characteristics of H. parasuis in China, 810 suspected infection samples, including lung tissues and pleural effusions, were systematically analyzed. These samples were collected between 2022 and 2024 from six major pig-producing provinces in China. The analysis revealed a national infection rate of 52.10% (422/810), with Jiangxi Province exhibiting the highest prevalence (71.76%). Seasonal analysis indicated significantly higher incidence rates during winter (66.29%) and spring (60.45%) compared to summer (34.81%) and autumn (46.46%). Serotyping of 56 H. parasuis isolates demonstrated that serotype 5 (42.86%) and serotype 12 (19.64%) were predominant, while 10.71% of the strains were nontypeable. Notably, Jiangxi Province displayed a single-serotype profile, whereas other provinces exhibited multiple-serotype cocirculation patterns. Virulence gene analysis revealed the universal absence of HPM-1370 and the consistent presence of vta3 across all isolates. Serotypes 4 and 8 exclusively harbored the vta gene cluster, while serotype 5 retained other target genes despite lacking HPM-1370. The HPM-1371 gene was detected only in serotypes 5 and 14. Serotypes 1, 11, 12, and 13 exhibited a combination of conserved wza-vta1-vta2 -vta3 genes, although 36.37% (4/11) of serotype 12 isolates lacked the wza gene. Serotypes 2 and 7 carried only wza and vta3 genes. Animal challenge experiments demonstrated marked differences in strain pathogenicity: the H5-1 strain induced 100% mortality with acute septicemia, widespread alveolar destruction, and fibrinous exudation; the H12-1 strain caused 50% mortality accompanied by severe pleural adhesions and hemorrhagic lesions; and the H7-1 strain resulted in 33.33% mortality with localized pulmonary damage. These findings provide essential evidence for the development of targeted prevention and control strategies against H. parasuis infection.